Studies on the Occurrence and Distribution of AM Fungi in Sugar Mill Effluent Polluted Soils in Nellikuppam Region of Cuddalore District - Ramakrishnan2, M. Ezhil Bama1*; K. (Journal of Phytology, 2010)
The occurrence and distribution of Arbuscular Mycorrhiza (AM) fungi on the sugar mill effluent polluted soil was examined.Â Twenty three species of AM fungi belonging to five genera viz., Acaulospora, Gigaspora, Glomus, Sclerocystis and Scutellospora were identified from the soil taken around ten plant species.Â Among ten plant species studied, only eight species were colonized and also the percentage root colonization was less in polluted soil. The number of AM spores were also less in polluted soil when compared to non-polluted soil. The increased levels of micronutrients and heavy metals were noticed in polluted soil, which caused reduction in the AM propagules. Key words: Sugar mill effluent, AM fungi, Polluted soil <span style="line-height: 110%; font-variant: normal !important; font-family: ";Book Antiqua";,";serif";; letter-spacing: -0.3pt; font-size: 7pt; font-weight: normal; mso-font-kerning: 0pt; mso-no-proof: no; mso-fareast-language: EN-SG; mso-ansi-language: EN-SG;" lang="EN-SG">M. Ezhil Bama and K. Ramakrishnan. Studies on the Occurrence and Distribution of AM Fungi in Sugar Mill Effluent Polluted Soils in Nellikuppam Region of Cuddalore District. J Phytol 2/1 (2010) 91-95.